Analisis Kajian Etnomatematika pada Bangunan Istana Langkanae - Muhammad Rusli Baharuddin; Rosmalah Yanti; Andi Wafda (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2023)
This study aims to determine ethnomathematics studies on the Langkanae palace building in the city of Palopo. This type of research is descriptive qualitative. The main instrument is the researcher and the instruments used are interview guidelines, literature and documentation. The research technique used was through interviews, literature study, and documentation with qualitative data analysis consisting of 3 stages, namely data reduction, data presentation and drawing conclusions, while to test the validity of the data using the triangulation method by comparing data from documentation with literature and data from interviews with literature study data. After this research was carried out, two ethnomathematics study results were obtained, namely (1) The concept of two-dimensional shapes found in the Langkanae palace building contained 7, namely triangular shapes, square shapes, rectangular shapes, rhombus shapes, trapezoidal shapes, hexagon shapes, and octagon shapes. (2) The concept of arithmetic operations on the Langkanae palace building is on the concept of the history of the establishment, the number and height of the parts of the Langkanae palace building. The finding in this study is that there is a difference in the year of establishment between sources from the palace and sources from literature.